2004
DOI: 10.1111/j.1365-2249.2004.02458.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of T cell receptor-αchain knock-out mice to ultraviolet B light and fluorouracil: a novel model for drug-induced cutaneous lupus erythematosus

Abstract: SUMMARYThe anticancer agent 5-fluorouracil (FU) frequently induces cutaneous lupus erythematosus (LE) lesions on sun exposed sites. Based on this observation, we have tried to establish a cutaneous LE model of C57BL/6 J (B6) mice, B6 T cell receptor (TCR)-a -/-mice and B6 TCR-d -/-mice treated with FU and/ or ultraviolet B light (UVBL) in order to clarify the role of T cells and the cytokine profile of cutaneous lupus lesions. Cutaneous LE-like skin lesions could be induced in TCR-a -/-mice with low FU (0·2 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 58 publications
0
20
0
1
Order By: Relevance
“…Studies in a murine model for drug-induced cutaneous lupus erythematosus demonstrated that ultraviolet might enhance the function of skin  T cells that were involved in skin lesions [27]. Therefore, EBV-infected  T cells may play an important role in the skin lesions of HV.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in a murine model for drug-induced cutaneous lupus erythematosus demonstrated that ultraviolet might enhance the function of skin  T cells that were involved in skin lesions [27]. Therefore, EBV-infected  T cells may play an important role in the skin lesions of HV.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore plausible to speculate that these chemotherapeutic agents translocate SSA/Ro antigen to the surface of cultured keratinocytes in a manner similar to UVB light. Interestingly, it has been shown that a combined treatment of FU and UVB strongly induces cutaneous-LE-like eruptions in mice [11, 12]. The tendency that DLE-like eruptions are located in sun-exposed areas of the skin further suggests that ultraviolet rays and these anticancer agents cooperate in inducing these skin symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The exact pathomechanism eliciting SCLE by 5-FU or capecitabine is not yet fully known. Yoshimasu et al 14 showed that T-cell receptor-alpha chain knockout mice developed cutaneous lupus erythematosus when treated with 5-FU and ultraviolet-B light. Whereas 5-FU causes damage to the basal layers of the epidermis, ultraviolet-B light leads to the translocation of Ro antigens to the surface of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%